Humus content in chernozems typical of the Left-Bank Forest-Steppe of Ukraine in connection with global climate change - Dehtiarov, V. V.; Shcherbakov, O. Yu. (AgroChemistry and Soil Science, 2023)
The results of studying the influence of global climate change on the total humus content in typical chernozems (Haplic Chernozems (Profundihumic)) of the Left Bank Forest-Steppe of Ukraine are presented by studying the characteristics of the rate of humification-mineralization of organic matter in the soil.The research objectives include the following: analysis of scientific literature on changes in the total humus content in chernozem soils used in agricultural production for different times; determination of the current humus content in the studied soil; analysis of the climatic conditions of the selected region; comparison of the rates of mineralization of humus substances with the dynamics of climatic changes. The studies showed that the rates of humus mineralization in the soil layer of 0–10 cm during the analyzed period (92 years) were different. In the first 25 years, the fall in humus content averaged 0.036 % per year, in the next 15 years — 0.063 % per year. This was followed by a sharp decline in the rate of dehumification and for the last 22-year period amounted to 0.012 % per year. The reason for this may be the influence of climatic conditions on the processes of humification-mineralization. It was the increase in average annual air temperatures by 2.9 ° C, the increase in soil surface temperature by 1.6 ° C, along with a decrease in the amount of precipitation during the growing season by 40 mm that led to a decrease in soil moisture supply over the past 22 years. And this is the reason for the imbalance between the processes of humification and mineralization, in the direction of strengthening the latter.